Formation Control Strategy for Underactuated Unmanned Surface Vehicles Subject to Unknown Dynamics and External Disturbances with Input Saturation - Mu, Dong Dong; Wang, Guo Feng; Fan, Yun Sheng (International journal of control, automation, and systems, 2020)
This paper addresses the formation tracking control problem of multiple underactuated unmanned surface vehicles. Considering many actual situations, a practical formation control scheme, which is performed by using a leader-follower approach, minimum learning parameter technique, adaptive technology and so on. Firstly, a virtual unmanned surface vehicle is designed according to the location information of the leader unmanned surface vehicle to estimate the leader’s speed information while reducing the communication bandwidth. Secondly, a formation control law is designed to make the follower underactuated unmanned surface vehicles track the leader. Unknown dynamics and external disturbances are regarded as a whole and compensated by the minimum learning parameter technique instead of multi-layer neural network and the neural shunt model can handle multiple derivation problems of virtual control laws. Meanwhile, the robustness of the controlled system is improved through adaptive technology. Besides, an auxiliary design system is employed to constrain the output range of the control law. Finally, numerical simulations are implemented to prove the feasibility of the formation tracking control strategy.